All of a sudden and forever : help and healing after the Oklahoma City bombing - Barton, Chris; Xu, Nicole, 1994- (Minneapolis : Carolrhoda Books, 2020)
Released to coincide with the 25th anniversary of the Oklahoma City bombing, this book commemorates what was lost and offers hope for the future.
AD800
Keywords: Oklahoma City Federal Building Bombing, Oklahoma City, Okla., 1995 -- Juvenile literature; Victims of terrorism -- Oklahoma -- Oklahoma City -- Juvenile literature